The Correlation between EFL' Students Listening Anxiety with Listening Motivation in Intermediate Listening Classes - Sinta Chairani Hutapea; Aryuliva Adnan; Leni Marlina (Journal of English Language Teaching, 2020)
Motivation has important rules in listening skills because it can make students more independent to reach their goal. This research deals with the correlation between listening motivation and anxiety of students. The purpose of this research to examine the students’ listening motivation and whether it is in correlation with their listening anxiety or not. This research involved 60 students in English Department of Universitas Negeri Padang who have already taken intermediate listening class. This study was conducted in correlational research. The random sampling used in this research.  There will be used two kinds of open direct questionnaire; ELCMS and FLLAS questionnaire which contain the rating scale.The result of the study showed that they have no correlation between listening anxiety and listening motivation (r= -160). The finding of this research revealed that the high listening motivation the students have do not close probability the low listening anxiety they have. It is also possible they have  a high listening motivation.